430 Cranially Directed Upper Instrumented Vertebrae Screw Angles are Associated with Proximal Junctional Kyphosis in Adult Spinal Deformity Surgery. (April 2023) - Chen, Jeffrey; Longo, Michael; Chanbour, Hani; LaBarge, Matthew; Abtahi, Amir; Stephens, Byron; Zuckerman, Scott L.
Abstract : INTRODUCTION: The effect of the upper instrumented vertebral (UIV) screw angle in adult spinal deformity (ASD) surgery on surgical complications and patient outcomes remains understudied. METHODS: A single-institution, retrospective cohort study was undertaken from 2011-17. UIV screw angle was trichotomized into: 1) Positive: cranially-directed screws relative to the UIV superior endplate (2° ≤ Θ); 2) Neutral: screws parallel to the UIV superior endplate (-2° <Θ <2°); and 3) Negative: caudally-directed screws relative to the UIV superior endplate (-2° ≥ Θ). The primary outcome was PJK/F. Secondary outcomes included remaining mechanical complications, reoperation, and PROMs: Oswestry Disability Index (ODI), Numeric Rating Scale (NRS) back/leg, and EuroQol (EQ-5D). Regression controlled for age, BMI, postoperative sagittal vertical axis, and pelvic-incidence to lumbar-lordosis mismatch. RESULTS: Among 145 patients undergoing ASD surgery, UIV screw angles were: 35(24.1%) cranially directed, 24(16.6%) neutral, and 86(59.3%) caudally directed. PJK occurred in 47(32.4%) patients. The incidence of PJK was highest for patients with cranially-directed screws (51.43%, p = 0.022). Cranially-directed screws were independently associated with PJK (OR = 4.88, 95%CI = 1.85-13.5, p = 0.002) and PJF (OR = 3.06, 95%CI = 1.32-12.30, p = 0.015), with a threshold value of -8.9° on ROC analysis (AUC = 0.64, 95%CI = 0.55-0.74, p<0.001). There was no association between UIV screw angle and remaining mechanical complications, reoperations, or PROMs. In addition, cranially directed screw angle was associated with increased risk of PJK (OR = 5.56, 95%CI = 1.86-17.90, p = 0.003) in lower thoracic cohort (T8 or below, N = 37), but not in the upper thoracic group (T7 or above, N = 37). CONCLUSIONS: Positive, cranially-directed UIV screw angles significantly increased the odds of PJK/F but not other mechanical complications, reoperation, or PROMs. Meticulous attention should be paid to UIV screw angle to reduce PJK/F.